Wellness among nursing students: A qualitative study - Chonticha Amattayakong (2020)
© 2020 Elsevier Ltd Nursing students typically experience high levels of stress and anxiety in nursing schools, and this is often compounded by having to combine complex classroom theories with practice. Healthy behaviors are subsequently neglected, diminishing academic efficiency and personal wellbeing. Student nurses need to adopt healthy lifestyles since wellness has been shown to promote positive health outcomes. Nonetheless, studies on the perception of wellness, and descriptions of its facilitators and barriers in wellness promotion among nursing students remain limited. This qualitative descriptive study aimed to explore facilitators and barriers to promote wellness among nursing students in Thailand. Data was gathered using focus groups with 80 undergraduate third and fourth-year nursing students, comprising 64 females and 16 males. Four themes emerged from content analysis regarding the facilitators of promoting wellness: healthy living; belief in animism; self-optimism; and receiving support. Barriers to wellness were three themes of stressors involved in students’ lives: pressure from instructors; behaviors of staff nurses; and being perceived as untrustworthy. It is vital to promote wellness among nursing students to encourage their health care choices and to support them through their studies.